Influence of Oleic Acid on the Rheology and in Vitro Release of Lumiracoxib from Poloxamer Gels - Tailane Sant´Anna Moreira; Valéria Pereira de Sousa; Maria Bernadete Riemma Pierre (Frontiers Media S.A., 2010)
Abstract PURPOSE: Transdermal delivery of anti-inflammatory lumiracoxib (LM) could be an interesting strategy to avoid the side effects associated with systemic delivery, but it is ineffective due to the drug poor skin penetration. We have investigated the effects of oleic acid (OA), a lipid penetration enhancer, on the in vitro release of LM from poloxamer-based delivery systems (PBDS). The rheological behavior (shear rate dependent viscosity) and gelation temperature through measurements of optimal sol-gel transition temperatures (Tsol-gel) were also carried out in these systems. METHODS: In vitro release studies of LM from PBDS were performed using cellulose acetate as artificial membrane mounted in a diffusion system. The amount of LM released was divided by exposition area (µg/cm2) and these values were plotted as function of the time (h). The flux of the drug across the membrane (J) was calculated from the slope of the linear portion of the plot and expressed as µg/cm2. h -1. The determination of viscosity was carried out at different shear rates (γ) between 0.1- 1000 S-1 using a parallel plate rheometer. Oscillatory measurements using a cone-plate geometry rheometer surrounded by a double jacket with temperature varying 4-40°C, was used in order to determine Tsol-gel. RESULTS: Increase of both polymer and OA concentrations increases the viscosity of the gels and consequently reduces the in vitro LM release from the PBDS, mainly for gels containing OA at 10.0% compared to other concentrations of the penetration enhancer. Tsol-gel transition temperature was decreased by increasing viscosity; in some cases the formulation was already a gel at room temperature. Rheological studies showed a pseudoplastic behavior, which facilitates the flow and improves the spreading characteristics of the formulations. CONCLUSIONS: Taken together, the results showed that poloxamer gels are good potential delivery systems for LM, leading to a sustained release, and also have appropriate rheological characteristics. Novelty of the work: A transdermal delivery of non-steroidal antinflammatory drugs like lumiracoxib (LM) can be an interesting alternative to the oral route of this drug, since it was recently withdraw of the market due to the liver damage when systemically administered in tablets as dosage form. There are no transdermal formulations of LM and it could be an alternative to treat inflammation caused by arthritis or arthrosis. Then, an adequate delivery system to LM is necessary in order to release the drug properly from the PBDS as well as have good characteristics related to semi-solid preparations for transdermal application, which were evaluated through in vitro release studies and rheological behavior in this paper, respectively.